APLIKASI PRAKTIS SUPERVISI PENDIDIKAN ISLAM - Lydia Sartika; Sartika; Nur Asni (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Supervision of Islamic education is an activity that aims to improve the quality of the process and results of Islamic education. Supervision is known as evaluation in educational institutions, of course someone who is part of an educational institution, namely a teacher, must evaluate and supervise their work and their respective performance, not depending on the supervision of superiors.